THE PECULIARITIES OF THE MAIN ORE-FORMING COMPONENTS DISTRIBUTION IN THE FILIZCHAY FIELD OF THE SOUTHERN SLOPE OF THE GREATER CAUCASUS - Sattar-zadeh, N.; Imamverdiyev, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article has been devoted to the distribution of the main ore-forming components in Filizchay field of the southern slope of the Greater Caucasus. 3D model of the mineral elements of Filizchay field has been using "Leapfrog GEO" program. Analysis of the isothicknesses map clearly shows that the eastern flank of the deeper, shallow dipping part of the deposit is characterized by the greatest thickness where its thickness exceeds practically universally average value of this parameter according to the field. It has been found that zinc and lead distributions repeat practically each other. The western half of the body differs sharply from the eastern half by stable high (more than average value) contents. The overwhelming majority of zinc concentrations minimums and nearly all lead minimums are located in the eastern half which is generally characterized by the contents being below average. According to the copper concentrations distribution the deposit is very clearly divided into two parts – the southeastern part being thicker and richer and the northwestern part being relatively less thick and with contents being below average according to the field. The comparison of silver and lead isocontents’ maps indicates a close relationship of both elements as evidenced by the very similar nature of their spatial distribution within the deposit. As well as for lead one can be generally distinguish two halves in it that are generally differed from each other in the intensity of the silvermineralization – the northwestern being richer and the southeastern being relatively poorer. The boundary between these parts repeats mainly the boundary determined for lead not only according to the spatial position but also according to the main details of the outline. All the maxima of the silver mineralization are located in the northwestern half of the field, the most of which are located on the upper horizons. According to the intensity degree of the zinc, lead and silver mineralization manifestation in the deposit, two parts can be distinguished: the western one is richer where almost all maxima are concentrated and the eastern one is poorer which accounts for the most of the minima. The boundary between them passes approximately in the middle part of the body from the upper to the lower horizons; it nearly coincides with the direction of its fall and it is distinguished by complex outlines. The frequent isolines repeatability of the zinc and lead contents, the close spatial position of their maxima centers suggest a close positive correlation between them.